Preventing hospital‐acquired venous thromboembolism: Improving patient safety with interdisciplinary teamwork, quality improvement analytics, and data transparency. (December 2016) - Schleyer, Anneliese M.; Robinson, Ellen; Dumitru, Roxana; Taylor, Mark; Hayes, Kimberly; Pergamit, Ronald; Beingessner, Daphne M.; Zaros, Mark C.; Cuschieri, Joseph
Abstract : BACKGROUND: Hospital‐acquired venous thromboembolism (HA‐VTE) is a potentially preventable cause of morbidity and mortality. Despite high rates of venous thromboembolism (VTE) prophylaxis in accordance with an institutional guideline, VTE remains the most common hospital‐acquired condition in our institution. OBJECTIVE: To improve the safety of all hospitalized patients, examine current VTE prevention practices, identify opportunities for improvement, and decrease rates of HA‐VTE. DESIGN: Pre/post assessment. SETTING/PATIENTS: Urban academic tertiary referral center, level 1 trauma center, safety net hospital; all patients. INTERVENTION: We formed a multidisciplinary VTE task force to review all HA‐VTE events, assess prevention practices relative to evidence‐based institutional guidelines, and identify improvement opportunities. The task force developed an electronic tool to facilitate efficient VTE event review and designed decision‐support and reporting tools, now integrated into the electronic health record, to bring optimal VTE prevention practices to the point of care. Performance is shared transparently across the institution. MEASUREMENTS: Harborview benchmarks process and outcome performance, including patient safety indicators and core measures, against hospitals nationally using Hospital Compare and Vizient data. RESULTS: Our program has resulted in >90% guideline‐adherent VTE prevention and zero preventable HA‐VTEs. Initiatives have resulted in a 15% decrease in HA‐VTE and a 21% reduction in postoperative VTE. CONCLUSIONS: Keys to success include the multidisciplinary approach, clinical roles of task force members, senior leadership support, and use of quality improvement analytics for retrospective review, prospective reporting, and performance transparency. Ongoing task force collaboration with frontline providers is critical to sustained improvements. Journal of Hospital Medicine 2016;11:S38–S43. © 2016 Society of Hospital Medicine